A weekend with Diego Rivera - Braun, Barbara, 1939- (New York : Distributed by St. Martin's, 1994)
Spend a weekend with the Mexican artist and learn about his life and work. Includes reproductions of his murals, paintings, and drawings.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.9
3-6
4-6
Keywords: Rivera, Diego, -- 1886-1957 -- Juvenile literature; Rivera, Diego, -- 1886-1957.; Rivera, Diego, -- 1886-1957.; Artists -- Mexico -- Biography -- Juvenile literature; Artists; Mexican artists -- Biography